Taylor–Couette flow of a fractional second grade fluid in an annulus due to a time-dependent couple - Imran, M.; Kamran, M.; Athar, M.; Zafar, A. A. A. (Nonlinear Analysis: Modelling and Control, 2011)
Exact solutions for the velocity field and the associated shear stress, corresponding to the flow of a fractional second grade fluid between two infinite coaxial cylinders, are determined by means of Laplace and finite Hankel transforms. The motion is produced by the inner cylinder which is rotating about its axis due to a time-dependent torque per unit length 2πR1ft2. The solutions that have been obtained satisfy all imposed initial and boundary conditions. For β → 1, respectively β → 1 and α1 → 0, the corresponding solutions for ordinary second grade fluids and Newtonian fluids, performing the same motion, are obtained as limiting cases.